DARI SUTET MENUJU TEOLOGI BERBASIS EKOLOGI (TINJAUAN HADIS-HADIS PELESTARIAN LINGKUNGAN, KESEHATAN, DAN LAYANAN PUBLIK - Munawir Munawir (UIN Siber Syekh Nurjati Cirebon, 2014)
This is the discussion about SUTET and the problems surrounding, whichare the environmental conservation and public service. Through the study of many related hadis, found thatÂ environmental conservation and public service are basic value in Islam. These piety (environmental conservation and public service) are the integral part from humanâ€™s piety to God. Being religious is not only about being good to God, but also to universe. Then by this spirit created a theology concept on ecology basic.Â Key Words: Environmental Conservation, Public Service, Piety